Looking up [videorecording (DVD)] - Armon, Eitan; Lefkowitz, Jay; Benegas, Willie (X4 Pictures, 2026)
Eitan Armon, a young man facing encroaching blindness, decides to let go of everything he can't control and climb Yosemite's most epic granite wall, El Capitan.